Influence of Crown Material and Margin Position on Gingival Health - Abdulaziz A Asiri; Abdulaziz S Alasmari; Abdulaziz M Asiri; Abdulrahman H Alasiri; Mohammed Y Asiri; Ali J Almufarrij; Mohammad Almagbol; Mohammed Alfarsi (The Bioscan, 2024)
Background: Badly broken teeth are often restored with crowns (1), which should be compatible with existing hard and soft tissues and fulfill the functional and aesthetic requirements as well. Objectives: to provide the patients with an evidence-based treatment by assessing the treatment outcome of crowning teeth. Determines the effect of the crown material on the gingival health. Methods: Sixty-nine patients, which has had their teeth crowned in the dental clinics of the college of dentistry at King Khalid University, have been evaluated to assess the influence of the crowns material and margin location on the gingival health. The crowned teeth were compared to their sound contralateral counterparts in a split-mouth cross-sectional study design by the same examiner. Results: Bleeding, mobility, color and recession were statistically significant with crowned in comparison to contra lateral (p ≤0.05). Bleeding and mobility increases in contra-lateral compared to crowned. And abnormal color increases significantly in crowned compared to contra lateral (p<.01). as well, recession grade I increases in contra lateral, where grade II recession was significantly higher in crowned (p<.01). Conclusion: Restoring a tooth with a suitable crown ought to be considered as the treatment of choice to reduce the risk of plaque retention to maintain prolonged dental health.